Poetical discourse analysis of a Tamil song Ovvoru Puukkalumee - Perumal, Thanalachime; Muthusamy, Paramasivam; K. Karunakaran, (M S Thirumalai, 2013)
This study is an attempt to analyze the Tamil movie song ‘Ovvoru PuukkaLumee ’ meaning ‘every flower’ from the Tamil movie 'Autograph'. This song is one of the popular songs of P. Vijay, a Tamil lyricist. The texture discourse of this song will be analyzed in terms of grammatical and lexical usages found by making use of discourse analysis.